Difusão do conhecimento em ciências ambientais: perspectivas e desafios na gestão da comunicação - Vasconcelos, Marcus Aurelius de Oliveira (2013)
This research aims to study the diffusion of knowledge in environmental sciences through management communication. Initially, it is the analysis of the actions, strategies and types of organization used by Prodema Network managers for knowledge social diffusion produced in the Graduate Program in Environment and Development at the Federal University of Sergipe. It seeks to identify and analyze the perspectives, problems and challenges encountered in the management of scientific knowledge produced in the period 1997-2012 and to propose a collaborative knowledge computer management network system (Web platform ). The research methodology lies in ethnography. The research is exploratory in nature, interdisciplinary and applied full active participant type. The method adopted is inductive - descriptive and dialogic. The ones who participated in this study were the program managers who interspersed moments holding the positions of vice coordination and coordination, as well as playing the role of research supervisors and the Post – Graduate Development and Environment students. The main instruments to collect selected information were participant observation, free observation, semistructured interview, standardized questionnaires, oral stories and documentary research. The data collected were analyzed using methodological triangulation (DENZIN, 2006). The preliminary results of the research brought to light three important elements. The first element refers to the knowledge social diffusion dissociated of institutional, political and organizational dimensions of the university management. In this context, the difficulties of institutionalized scientific knowledge management presented themselves concentrated in three types: restrictive, driving and ubiquitous. The second element corresponds to environmental sciences seeking the production of new knowledge from the union of existing knowledge in the areas of human knowledge related to problems for which solutions are sought. The third element relates to knowledge management, which uses techniques of administration area to capture, build, operate and produce new knowledge. It was identified that there is a predominance of one of the types of difficulties encountered according to the historical period analyzed. The challenges faced by managers cover the following action plans or plans of institutional organization: financial administrative.